Pengaruh Availability Product, Store Atmosphere, dan Fasilitas Pendukung Produk terhadap Keputusan Pembelian Produk Glico Wings Ice Cream - Afandi, Muhammad Sulaeman; Handayani, Langgeng Sri (Ekonomis: Journal of Economics and Business, 2024)
This research was conducted to determine the influence of product availability, store atmosphere, and supporting facilities partially on purchasing decisions. The research method used was quantitative with 67 Glico Wings ice cream customers as respondents. The data collected is the result of a questionnaire. Prerequisite testing was carried out with SPSS 25 software. The results of this research partially show that store atmosphere has a negative and insignificant effect on purchasing decisions. Product availability and supporting facilities have a positive and significant influence on purchasing decisions.